Urgensi Penerapan Interdependent Airspace Governance Untuk Optimalisasi Tata Kelola Ruang Udara Nasional Sebagai Antisipasi Open Sky Policy - Wahyu Beny Mukti Setiyawan; Nurul Hidayah; Andi Chaerul Sofyan (Universitas Batanghari Jambi, 2020)
Indonesia as an archipelago state has a national airspace of 5,180,053 km². Indonesia's airspace is located in a strategic position between the continents of Asia and Australia which makes Indonesia one of the busiest air routes in the world. Therefore, the management of air space is a vital matter that must be emphasized through various legal instruments. The sovereignty of Indonesian air space is affirmed in Article 49 paragraph (2) of the 1982 International Law of the Sea Convention which was ratified by Law Number 17 of 1985 concerning Ratification of the United Nations Convention on the Law of the Sea. This article explicitly regulates the legal status of archipelagic waters, air space over archipelagic waters and the seabed as well as the land below. So far, territorial sovereignty that is complete and exclusive is regulated in Law Number 1 of 2009 concerning Aviation, but it does not specifically regulate the boundaries of Indonesia's sovereign air space, either vertically or horizontally. The national airspace of a country is completely closed to foreign aircraft, both civilian and military, so it must be with the permission of the underworld, either through bilateral agreements or multilateral agreements, so that a country's national air space can be traversed by foreign aircraft. Such closed nature can be understood considering that air space is a very vulnerable medium of movement when viewed from the point of view of under-state defense and security. Attacks using aircraft have many advantages and conveniences that can exploit the vulnerability of an air space, such as its fast (speed), wide range, surprise, optimal penetration. This is what prompts each country to adopt its national airspace protection standards which are strict and rigid. Flights between countries are fully regulated through the Bilateral Air Transport Agreement (BATA). Without BATA, the state cannot provide air transportation services to a country. BATA itself is a form of implementation of state sovereignty in air space that is complete and exclusive in the midst of globalization challenges, such as aviation liberalization (Open Sky Policy). Referring to the Open Sky Policy, this policy allows air carriers to make decisions on routes, capacities, prices and various options for flight activities.